PENINGKATAN KETRAMPILAN KELOMPOK PETANI WILAYAH SRENGSENG JAKARTA BARAT - Ruswanti, Endang; Hapsari, Nia Puspita (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
AbstractUtilization of vacant land so far, is used by farmers with traditional farming with conventional marketing. Utilization of land managed by families tends to be carried out by farmer mothers starting from planting, maintaining plants to harvest. Mother's leisure activities are used for less productive things. The problem is that the group of farmers in the village of srengseng lack knowledge that is beneficial to the family. For this reason community service solutions increase the knowledge of mothers. By means of skills that are more productive and can improve family welfare. The method of community service is to spend farmers with the knowledge they need. Giving religious knowledge to children, mothers receive simple financial guidance, learn motivational and entrepreneurial theories, how to make organic fertilizer, how to grow organic plants. This dedication is carried out on the basis of organic research that received grants from DIKTI in 2017 and 2018. The research output is the national journal of community service and special outcomes are mothers can utilize the land with organic investment and self-employment, and educate children with Islamic religion. Keywords: Improved skills, farmers, srengseng AbstrakPemanfaatan lahan kosong selama ini, digunakan oleh para petani dengan bertani tradisional dengan pemasaran konfensional. Pemanfaatan lahan yang dikelola oleh keluarga berkecenderungan dilaksanaan oleh ibu-ibu petani mulai dengan penanaman, pemeliharaan tanamansampai panen. Kegiatan ibu-ibu diwaktu senggang digunakan untuk hal yang kurang produktif. Masalahnya kelompok ibu-ibu petani kelurahan srengseng kurang memiliki pengetahuan yang bermanfaat untuk keluarga. Untuk itu solusi pengabdian masyarakat meningkatkan pengetahuan ibu-ibu. Dengan melalui ketrampilan yang bermakna agar lebih produktif dan dapat meningkatkan kesejahteraan keluarga. Metode pengabdian masyarakat adalah dengan membelaki ibu-ibu petani dengan pengetahuan yang dibutuhkan. Memberi pengetahuan agama pada anak-anaknya, ibu-ibu mendapat bimbingan pengetahuan keuangan sederhana, belajar teori motivasi dan kewirausahaan, cara membuat pupuk organic, cara menanam tanaman organic. Pengabdian ini dilaksanakan sehubungan dengan hasil penelitian tentang organic yang mendapat hibah dari DIKTI tahun 2017 dan 2018. Luaran penelitian adalah jurnal nasional pengmas dan luaran khusus adalah ibu-ibu dapat memanfaatkan lahan kosong dengan menanam organic dan wirausaha snek, maupun mendidik anak-anak dengan agama Islam. Kata kunci: Peningkatan keterampilan, petani, srengseng